A narrative inquiry of Indonesian EFL students’ writing experiences in the morning English talks program - Syarifudin, Syarifudin; Azhar, Muhammad Anis; Jannah, Miftahul; Muslimin, Afif Ikhwanul (Edelweiss Applied Science and Technology, 2025)
This study investigates the writing experience of Indonesian EFL students in the Morning English Talks (METs) activity, a community language learning task that integrates extensive reading with reflective discussion. Implemented at an Islamic State University in West Nusa Tenggara, this qualitative study applied a narrative inquiry approach with three purposively selected participants. Data were collected through in-depth semi-structured interviews and complemented by students’ reflective journals. Thematic analysis showed that the METs program was significant in the construction of students’ writing through the improvement of vocabulary, grammatical awareness, and the ability to organize and express ideas. Reading and dialogic discussion regularly also helped to construct critical thinking and writing confidence. The use of WhatsApp as an online space facilitated continuous learning beyond the classroom and collective meaning-making. While the findings are rich in conceptual insight into the benefits of community-based literacy practice, the small number of participants suggests a need for further studies with larger, more diverse participant groups and qualitative and quantitative designs. The study has practical significance for EFL instructors who desire to combine writing instruction with low-tech, student-mediated approaches that bridge formal and informal learning environments.